A Study On The Integration Of Heritage Components Into The Iranian Primary School Curriculum - Barghi, Rabeeh (2021)
This study investigated Iranian primary school curriculum from different perspectives in order to describe and further explain current situation of integrating heritage component into the curriculum. First approach involved examining all primary textbooks as the main resources represent the ideal stage. The study then was keen to find out the way teachers, administrators, and educational experts as the key stakeholders perceive the situation of heritage education and the extent to which it is being implemented.